2015
DOI: 10.1002/jid.3098
|View full text |Cite
|
Sign up to set email alerts
|

Technology Gaps and Capacity Issues in African Insurance Companies: Selected Country Evidence

Abstract: This paper describes a variety of approaches used to assess the efficiency of a sample of major insurance companies in Angola and Mozambique between 2003 and 2012. Several data envelopment analysis estimates were generated using bootstrap technique, as this allowed the use of confidence intervals and the correction of a biased perception noted in the core estimates, in order to test the significant differences identified in efficiency levels and the input‐decreasing/output‐increasing potentials in the meta‐fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Implementation of information and communication technologies can bring new opportunities for insurance business development. Different positive effects of this process are widely discussed in the literature (Pagano et al, 2019;Gatteschi et al, 2018;Barros et al, 2017;Forman et al, 2011;Neirotti et al, 2007). The research study showed the gap between the theoretical background and the practical realisation of digitalisation processes in insurance.…”
Section: Discussionmentioning
confidence: 94%
“…Implementation of information and communication technologies can bring new opportunities for insurance business development. Different positive effects of this process are widely discussed in the literature (Pagano et al, 2019;Gatteschi et al, 2018;Barros et al, 2017;Forman et al, 2011;Neirotti et al, 2007). The research study showed the gap between the theoretical background and the practical realisation of digitalisation processes in insurance.…”
Section: Discussionmentioning
confidence: 94%
“…There are few studies on insurers using the DEA meta-frontier approach (see e.g Wanke & Barros, 2016;Barros & Wanke, 2017)…”
mentioning
confidence: 99%